One Class, One Pot, One Tree as a Sustainability Design Strategy in Environmental Management at SMP Negeri 1 Warureja - Ismiyati Hanum; Didit Widiatmoko Soewardikoen; Irwan Sudarisman (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
Environmental issues have become a global concern that requires serious attention, including in the education sector. This study aims to evaluate the "One Class, One Pot, One Tree" program as a sustainability design strategy for environmental management at SMP Negeri 1 Warureja. The research employed a descriptive qualitative approach with participants including students, teachers, and the principal. Data were collected through observation, interviews, and documentation, and analysed thematically. The findings revealed that student participation reached 85%, reflecting the success of the experiential learning approach. The program also positively impacted the school environment, with an increase in green spaces by 35% (52.5 m²) and a reduction in the average environmental temperature by 1.5°C. However, challenges such as limited water resources and busy schedules were identified. Local community involvement and integration with the curriculum present opportunities to enhance program sustainability. In conclusion, the program not only improves students' environmental awareness but also establishes a sustainability education model that can be adopted by other schools in Indonesia.